ANALISIS PENGARUH MAQOSID SYARIAH TERHADAP FATWA DSN-MUI TENTANG MUROBAHAH - Hanif, Ahmad; Susanto, Hari; Erismen Armen, Rio (Universitas Ibn Khaldun Bogor, 2022)
The study is intended to review how the implementation of maqosid sharia in fatwa-fatwa DSN-MUI is about murabahah and see how far the application of maqosid sharia’s influence on the fatwa-fatwa DSN-MUI is about murobahah. In implementing maqosid sharia in his fatality DSN MUI does not include the sharia’s intention as specifically but maqosid is found in the sense of the tarjih rules,’ fiqh rules and other ijtihad mechanisms. Maqosid sharia is also very influential in fatwa DSN-MUI, especially in the following consideration: opinion selection (tarjih), looking for even better outcomes by leaving behind majority scholars’ income (jumhur), considering the fatwa dynamics of change, and creating islamic akkad solutions and alternatives, considering the results of an akkadian.